Manufacturing method of highly dispersed Ag / C composite materials for secondary batteries
Patent Information
- Application Number
- KR1020250170416
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-11-12
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2045-11-12
Smart Images

Figure 112025126412120-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a composite material composed of silver and carbon, and more specifically, to a method for manufacturing a highly dispersed silver / carbon composite material that can improve the electrode durability and performance of a secondary battery by finely controlling the size of silver nanoparticles and ensuring uniform dispersion. Background Technology
[0002] Secondary batteries are rechargeable batteries that can be charged using an external power source and convert stored chemical energy into electrical energy upon discharge. Lithium-ion batteries, a representative example, are widely used in various fields such as portable electronic devices, electric vehicles, and energy storage systems (ESS) due to their high energy density and excellent cycle characteristics.
[0003] The basic structure of a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator; in particular, the electrode is a key component that serves as a pathway for electron movement and where the insertion and extraction of lithium ions repeatedly occur. The structural stability, conductivity, and reaction uniformity of the electrode directly affect the capacity retention rate and lifespan of the secondary battery.
[0004] Recently, conductive composite materials that combine metal nanoparticles and carbon materials have been attracting attention to improve electrode conductivity and ensure durability. Among them, silver / carbon (Ag / C) composite materials have the advantage of being able to simultaneously utilize the excellent electrical conductivity of silver (Ag) and the lightweight, chemical resistance, and electrode structure support properties of carbon, thereby suppressing the increase in electrode resistance and maintaining a uniform current distribution during repeated charging and discharging.
[0005] However, in conventional silver / carbon (Ag / C) composite material manufacturing methods, silver (Ag) particles were formed relatively large or had non-uniform particle sizes, which resulted in reduced dispersibility within the electrode. Consequently, the electrochemical active surface area was limited, leading to particle aggregation and detachment during repeated charging and discharging, which resulted in low durability when applied to secondary batteries. Prior art literature
[0006] Republic of Korea Published Patent No. 10-2023-0124793 (August 28, 2023) The problem to be solved
[0007] The present invention provides a method for manufacturing a silver / carbon composite material that can simultaneously improve the electrochemical durability and performance of a secondary battery by controlling the size of silver particles finely and uniformly to improve the dispersion between particles and strengthen the bonding force with the current collector within the electrode.
[0008] Other detailed objectives of the present invention will be clearly understood and grasped by experts or researchers in the art through the specific details described below. means of solving the problem
[0009] To solve the above problem, the present invention, as an embodiment, provides a method for manufacturing an Ag / C composite material for a secondary battery electrode using a silver (Ag) precursor and a carbon (C) carrier, wherein the silver precursor is dissolved in a solvent to produce silver ions (Ag + A method for manufacturing an Ag / C composite material for a secondary battery electrode is presented, comprising: a first step of forming a uniform solution containing ), a second step of mixing the solution formed in the first step with a carbon carrier and aging it so that silver ions are uniformly adsorbed on the carbon surface, a third step of reducing the mixed solution of the silver precursor, solvent, and carbon carrier obtained through the second step to form silver nanoparticles on the carbon carrier, and a fourth step of filtering, washing, drying, and grinding the mixed solution obtained through the third step to obtain an Ag / C composite material in the form of uniform fine particles.
[0010] At this time, in the first step above, a complex ionizing agent is additionally added to the solution in which the silver precursor is dissolved in a solvent, and the complex ionizing agent may be ammonia (NH3) or carbon monoxide (CO).
[0011] Meanwhile, in the first step above, the solvent is at least one of ethylene glycol (EG), propylene glycol (PG), glycerol, and ethanol, and in the third step above, the mixed solution obtained through the second step above can be heated to a temperature of 100 to 180 ℃ to reduce silver ions.
[0012] In addition, drying in the fourth step above is performed under vacuum or nitrogen atmosphere conditions of 25 to 30 ℃, thereby preventing oxidation and aggregation of silver nanoparticles. Effects of the invention
[0013] The method for manufacturing an Ag / C composite material according to the present invention can effectively achieve the micronization and uniform dispersion of silver particles. Accordingly, the Ag / C composite material manufactured improves the electronic conductivity within the electrode and ensures the uniformity of the electrochemical reaction, thereby significantly improving the overall performance of the secondary battery.
[0014] In particular, through composite formation with carbon, silver can be controlled to be stably dispersed and mixed, and the uniformly dispersed silver (Ag) nanoparticles disperse the alloying sites with lithium and inhibit the growth of lithium (Li) metal dendrites, thereby improving stability during the charging and discharging process and simultaneously increasing the lifespan and durability of the secondary battery.
[0015] Other effects of the present invention will be clearly grasped and understood by experts or researchers in the art through the specific details described below or during the process of implementing the present invention. Brief explanation of the drawing
[0016] FIG. 1 is a flowchart illustrating a method for manufacturing a highly dispersed Ag / C composite material according to an embodiment of the present invention. FIG. 2 is a graph showing the results of a durability test of a secondary battery including an electrode with an Ag / C composite material prepared according to an example and a comparative example. Specific details for implementing the invention
[0017] The features and effects of the present invention described above will become clearer through the following detailed description in conjunction with the attached drawings, and accordingly, a person skilled in the art to which the present invention pertains will be able to easily implement the technical concept of the present invention. Since the present invention is susceptible to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the present invention to specific disclosed forms, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention. The terms used in this application are used merely to describe specific embodiments and are not intended to limit the present invention.
[0018] The structure, function, and operation of the method for manufacturing a highly dispersed Ag / C composite material according to the present invention will be explained below with reference to the attached drawings.
[0019] FIG. 1 is a flowchart illustrating a method for manufacturing a highly dispersed Ag / C composite material according to an embodiment of the present invention.
[0020] A method for manufacturing an Ag / C composite material according to the present invention comprises: i) a first step of mixing an Ag precursor and a solvent; ii) a second step of introducing a solution of the Ag precursor and the solvent into a carrier; iii) a third step of heating the mixed solution to form Ag nanoparticles; and iv) a fourth step of post-processing by washing, drying, and grinding. Each step may include optional or alternative embodiments.
[0021] Each step is explained in detail below.
[0022] In the first step, an Ag precursor is mixed with a suitable solvent to provide silver (Ag) particles to be supported on a carrier (S10).
[0023] The silver precursor is intended to provide Ag particles to be supported on a carrier and is not limited to a specific compound. For example, various metal salts or metal acids such as silver nitrate (AgNO3), silver acetate (AgC2H3O2), silver chloride (AgCl), and silver oxide (Ag2O) can be used as silver precursors. In the following description, silver nitrate (AgNO3) was used as the silver precursor.
[0024] The content of Ag used in the present invention is not particularly limited, but can be adjusted to about 5 to 50 weight percent relative to the total weight of the Ag / C composite material, and more preferably, a range of 5 to 25 weight percent is suitable.
[0025] If the Ag content is less than 5 wt%, the electrochemical performance in the secondary battery and the effect of suppressing lithium dendrite (Li Dendrite) formation may be weak. Conversely, if the Ag content exceeds 50 wt%, the aggregation of metal nanoparticles intensifies during repeated charging and discharging of the secondary battery, which may lead to a decrease in the dispersibility and electrode performance of the composite material.
[0026] Meanwhile, the solvent mixed with the silver precursor is not limited to a specific solvent, but a solvent capable of uniformly mixing the silver precursor is preferred. For example, the solvent may be selected from distilled water, ethylene glycol (EG), propylene glycol (PG), a solvent mixed with glycerol and ethanol.
[0027] The mixing of the precursor and the solvent can be carried out in a reactor such as a double-jacketed reactor, and the solvent and, if necessary, additives that aid in dissolution in the solvent can be introduced. The additives can be selected from ethanol, acids, bases, dispersants, etc.
[0028] A silver precursor of the target concentration is slowly added to the solvent and completely dissolved. At this time, the stirring speed can be set to 200 to 1000 rpm. The temperature of the mixed solution is appropriately 20 to 100 ℃. If heated above 100 ℃, the silver particles may be reduced and aggregate. The concentration and volume of the dissolved silver precursor (solution) are determined based on the calculation of the loading amount in the subsequent step (e.g., final silver content 5 to 50 wt%).
[0029] Meanwhile, a complexing agent may be added to the mixture of the silver precursor and the solvent as needed. The complexing agent may be injected in a liquid state or pre-dissolved in the solvent before injection.
[0030] Complex ionizers are silver ions (Ag + Various substances such as ammonia (NH3), carbon monoxide (CO), and amine compounds can be used to lower the activity of free silver ions, control nucleation, and inhibit particle aggregation during the growth stage.
[0031] In particular, when ammonia (NH3) or carbon monoxide (CO) is used as a complex ionizing agent, silver (Ag) ions are complex ionized, so the reduction rate is gently controlled and nucleation and growth are balanced. As a result, the size of the silver nanoparticles formed is small and the distribution is uniform, so when applied to an electrode, the current is not concentrated in a specific area but is distributed uniformly.
[0032] In addition, CO is adsorbed onto the silver surface during the reduction process, thereby suppressing the formation of silver oxide (Ag2O) and the aggregation of silver particles, which maintains the conductivity of the silver particles even during repeated charging and discharging. Accordingly, this contributes to securing long-term stability of the electrode structure and improving charge and discharge durability.
[0033] In the second step, a carrier for supporting the silver precursor is prepared, and a solution of the Ag precursor and a solvent is mixed and introduced into the carrier (S20).
[0034] The material used as the carrier is not specified, and any material capable of stably fixing silver (Ag), such as magnesium oxide, silicon, and carbon, can be used as the carrier, but it is preferable to use carbon.
[0035] Carbon is widely used as an anode material for secondary batteries and possesses structural characteristics capable of storing lithium (Li), allowing it to stably maintain electrode activity during charging and discharging.
[0036] Here, carbon-based materials such as activated carbon, carbon black, carbon nanotubes, and graphene can be used as carbon-based carriers, and known carbon blacks such as furnace black, acetylene black, vulcan carbon, and ketjen carbon can be used as carbon black.
[0037] The particle size of the carbon is preferably 40 to 80 nm. If the particle size of the carbon powder exceeds 80 nm, there is a concern that battery performance may decrease due to reduced lithium ion mobility caused by the volume expansion of the storage material during the charging and discharging process. On the other hand, particles smaller than 40 nm have limited lithium storage capacity, making it difficult to expect sufficient electrode activation.
[0038] Once the carrier is prepared in this manner, a metal precursor solution is introduced into the prepared carrier and mixed uniformly. The mixing process is not limited to a specific device and various stirring devices, such as a ribbon mixer or a planetary mixer, can be utilized. By ensuring that the Ag precursor is uniformly dispersed on the carbon surface, the dispersion of the final Ag / C composite material can be increased.
[0039] In the third step, silver ions are reduced from a silver precursor to form silver nanoparticles (S30). Additionally, as the silver ions are reduced to a carrier, an Ag / C composite material is formed in which silver particles are supported on the carrier.
[0040] The reduction performed in the present invention is solvent reduction, in which the reactor temperature is gradually raised to perform the reduction treatment when the solvent is near its boiling point. For example, alcohol-based solvents such as ethylene glycol generate protons near their boiling point, causing silver ions (Ag + ) metallic silver (Ag 0 It plays the role of reducing to ).
[0041] The appropriate reduction temperature is 100 to 180 ℃. At temperatures below 100 ℃, it is difficult to achieve sufficient reduction of silver ions, which may result in incomplete formation of metal particles. If the temperature exceeds 180 ℃, agglomeration between particles intensifies, leading to reduced dispersibility, and consequently, it is difficult to expect an improvement in the electrochemical performance of the secondary battery.
[0042] The size of the silver nanoparticles formed at this time has a direct effect on the electrode characteristics, so it is desirable to have a particle size of 200 nm or less, and more preferably, a size in the range of 10 to 100 nm is appropriate.
[0043] Silver particles larger than 100 nm may increase the expansion rate during the alloying process with lithium (Li), potentially reducing the stability of the electrode structure, while particles smaller than 10 nm may increase the proportion of amorphous silver, potentially reducing charge / discharge efficiency and dendrite suppression effects.
[0044] In addition, it is important that the surface of the reduced metal nanoparticles remains unoxidized by oxygen (O2). Therefore, it is desirable to inject an inert gas to reduce them in this step. If oxygen is present on the surface, lithium ions (Li + This reacts with oxygen to form an irreversible oxide (Li2O), which can impair the reversibility of the electrode and accelerate the formation of lithium dendrites, thereby affecting the battery's lifespan and stability.
[0045] In the fourth step, the Ag / C composite material formed through the mixing and reduction process is filtered, washed, dried, and ground to obtain the Ag / C composite material in powder form (S40).
[0046] First, the Ag / C composite material formed through the mixing and reduction process is separated from the reaction solution through a filtration process, and impurities are removed through a washing process.
[0047] Through this process, impurities such as by-products, reaction residues, or unreacted compounds generated during the reaction can be effectively removed. Meanwhile, washing can generally be performed using distilled water or alcohol-based solvents.
[0048] Next, the washed Ag / C composite material is subjected to a drying process to remove residual moisture and volatile impurities. The drying method is not particularly limited, and a vacuum oven or a convection oven may be used. Preferably, a vacuum oven is used to effectively remove moisture at a low temperature. If a convection oven is used, it is preferable to dry in a nitrogen (N2) atmosphere to prevent oxidation.
[0049] A drying temperature in the range of approximately 25 to 30°C is appropriate. Below 25°C, volatile substances are not sufficiently removed, which may leave residues in the composite material, potentially leading to a degradation of the battery's electrochemical performance. On the other hand, if the temperature exceeds 30°C, aggregation between metal particles occurs, increasing the viscosity of the electrode slurry and consequently raising concerns about reduced stability in the battery manufacturing process.
[0050] The drying time is not specifically limited, but about 6 to 24 hours is preferable. If it is less than 6 hours, it is difficult to completely remove impurities, and if it exceeds 24 hours, the process time increases unnecessarily and the aggregation of metal particles may be accelerated.
[0051] Next, the dried Ag / C composite material is pulverized through a grinding process to adjust the final particle size. The grinding method is not limited; for example, a high-speed mixer can be used to grind the dried Ag / C composite material into uniform fine particles. This process plays an important role in increasing the reaction surface area and improving the efficiency of the Ag / C composite material by uniformly adjusting the size of the reduced metal particles.
[0052] Grinding can generally be performed 1 to 2 times for 1 to 2 minutes, thereby ensuring the uniformity of the Ag / C composite particles. The more uniform the particles, the more consistently the electrochemical behavior of the electrode is maintained during the reaction, which can improve the performance and reliability of the battery.
[0053] The Ag / C composite material obtained through these filtration, washing, drying, and grinding steps exhibits excellent Ag dispersibility and high particle size uniformity. Therefore, not only is the charge and discharge efficiency of the secondary battery improved, but the durability of the secondary battery can also be significantly enhanced due to the fine Ag dispersion structure within the electrode.
[0054] The Ag / C composite material prepared according to the method of the present invention has a structure in which silver (Ag) nanoparticles are uniformly distributed in a high-dispersion state on a carbon carrier. This structural characteristic shortens the electron transport path within the electrode, thereby improving the electrochemical reaction efficiency of the secondary battery and effectively suppressing the formation of lithium dendrites during the charging and discharging process. In addition, the carrier, such as carbon, prevents the aggregation of metal nanoparticles, ensuring that the particle size and distribution remain stable even during long-term use.
[0055] Meanwhile, the Ag / C composite material manufactured according to the present invention can be applied as an active material for an electrode for a secondary battery. Specifically, the Ag / C composite material can be mixed with a polyvinylidene fluoride (PVDF) binder and an N-methyl-2-pyrrolidone (NMP) solvent to form a slurry, and then uniformly coated onto a current collector such as copper foil (Cu foil) and dried to form an electrode.
[0056] The electrode manufactured in this way secures excellent electrical conductivity and mechanical stability through Ag nanoparticles uniformly distributed on the surface of a carbon carrier, and the aggregation or detachment of Ag particles is suppressed even during repeated charge and discharge cycles. Therefore, the electrode using this Ag / C composite material can simultaneously achieve improved uniformity of current distribution, reduced electrode interface resistance, and inhibition of lithium dendrite growth.
[0057] Furthermore, secondary batteries manufactured using such Ag / C composite-based electrodes exhibit characteristics of high capacity retention and excellent durability even during prolonged charging and discharging, due to the structural stability and improved conductivity of the electrodes.
[0058] The silver / carbon (Ag / C) composite material manufactured in this way can secure high durability and a stable electrode structure, and as a result, provides the effect of simultaneously improving the lifespan and performance of the secondary battery.
[0059] Next, an example of manufacturing an Ag / C composite material according to one embodiment of the present invention will be described in detail. The following example is merely illustrative of one form of the present invention, and the scope of the present invention is not limited by the following example.
[0060] Examples
[0061] Composite Material Manufacturing
[0062] An Ag precursor mixed solution was prepared by mixing silver nitrate (Ag nitrate) as an Ag precursor with ethylene glycol solvent. Meanwhile, carbon (Super P, Emeris) was prepared as a support and introduced into a double-jacketed reactor. To mix and mature the Ag precursor and carbon, the Ag precursor mixed solution was added to the carbon using a peristaltic pump. At this time, the temperature of the double-jacketed reactor was set to 25 ℃, the Ag precursor mixed solution was introduced to ensure 15 wt% silver was supported, and the mixture was aged for 12 hours to ensure uniform Ag loading. Subsequently, the Ag precursor mixed solution containing carbon was maintained at 110 ℃ for 1 hour to reduce Ag ions to Ag metal, thereby producing an Ag / C composite material. After filtration and washing, the Ag / C composite material was dried in a vacuum oven at 30 ℃ for 12 hours. The Ag / C composite material was micronized through a grinding process, and finally, a 15wt% Ag / C composite material was manufactured.
[0063] Electrode Manufacturing
[0064] The manufactured Ag / C composite material was slurried with a PVDF (Polyvinylidene Fluoride) binder and NMP (N-Methyl-2-pyrrolidone), uniformly coated onto a copper foil (Cu foil) current collector, and dried to form an electrode.
[0065] Comparative example
[0066] Composite Material Manufacturing
[0067] A mixture was prepared by uniformly mixing carbon with 25 wt% Ag nanoparticles, which is higher than the 15 wt% Ag / C composite material prepared in the example.
[0068] Electrode Manufacturing
[0069] The prepared mixture was slurried with a PVDF (Polyvinylidene Fluoride) binder and NMP (N-Methyl-2-pyrrolidone), uniformly coated onto a copper foil (Cu foil) current collector, and dried to form an electrode.
[0070] Evaluation example
[0071] A coin-type secondary battery with lithium metal as the counter electrode was assembled using the electrodes prepared through the examples and comparative examples, and a cycle test was performed. In the experiment, the capacity retention relative to the initial capacity was evaluated by measuring the capacity for each cycle while repeating charge and discharge cycles under constant current conditions.
[0072] Referring to FIG. 2, the secondary battery using the Ag / C composite material of the example shows a significantly slower decrease in capacity retention rate even as the number of charge-discharge cycles increases compared to the secondary battery using the Ag / C composite material of the comparative example. This is thought to be because Ag nanoparticles are uniformly dispersed and supported on the surface of the carbon carrier, thereby suppressing particle aggregation or detachment during repeated charge-discharge processes. On the other hand, the secondary battery using the Ag / C composite material of the comparative example appears to have non-uniformity in current distribution within the electrode as simply mixed Ag nanoparticles aggregate and detach from the electrode surface, and consequently, shows a tendency for capacity to decrease rapidly as the cycle progresses. These results demonstrate that the Ag / C composite material of the present invention simultaneously improves electrode structural stability and electrochemical durability.
[0073] Although the detailed description of the present invention described above has been explained with reference to preferred embodiments of the invention, those skilled in the art or those with ordinary knowledge in the relevant technical field will understand that various modifications and changes can be made to the present invention without departing from the spirit and technical scope of the invention as described in the claims set forth below.
Claims
Claim 1 A method for manufacturing an Ag / C composite material for a secondary battery electrode using a silver (Ag) precursor and a carbon (C) carrier, comprising: a first step of dissolving a silver precursor in a solvent to form a homogeneous solution containing silver ions (Ag+); a second step of mixing the solution formed in the first step with a carbon carrier and aging it so that silver ions are uniformly adsorbed onto the carbon surface; a third step of reducing the mixed solution of the silver precursor, solvent, and carbon carrier obtained through the second step to form silver nanoparticles on the carbon carrier; and a fourth step of filtering, washing, drying, and grinding the mixed solution obtained through the third step to obtain an Ag / C composite material in the form of homogeneous fine particles, wherein in the first step, the solvent contains ethylene glycol; in the second step, the solution is mixed with a carbon carrier and aged for 12 hours so that silver ions are uniformly adsorbed onto the carbon surface; and in the third step, the mixed solution is heated to a temperature of 100 to 180°C so that silver is formed by solvent reduction of the solvent containing the ethylene glycol. A method for manufacturing an Ag / C composite material for a secondary battery electrode, wherein ions are reduced to silver nanoparticles, and in the fourth step, the drying is performed under vacuum or nitrogen atmosphere conditions of 25 to 30°C to prevent oxidation and aggregation of silver nanoparticles. Claim 2 A method for manufacturing an Ag / C composite material for a secondary battery electrode according to claim 1, wherein in the first step, a complex ionizing agent is additionally added to a solution in which a silver precursor is dissolved in a solvent, and the complex ionizing agent is ammonia (NH3) or carbon monoxide (CO). Claim 3 delete Claim 4 delete
Citation Information
Patent Citations
Method for fabrication of metal-coated carbon composite material and anode for a solid state battery using the same
KR1020230124793A
Nanostructured material loaded with noble metal particles
US20110014550A1